Pengaruh Kesadaran Wajib Pajak Sosialisasi Perpajakan dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak Reklame - Jihan Erilidya Kumalasari; Suhesti Ningsih; Sri Laksmi Pardanawati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to find out how Taxpayer Awareness, Tax Socialization, and Tax Sanctions have an impact on Billboard Taxpayer Compliance in Karanganyar Regency. Quantitative and associative methods are used. The Slovin formula was used to determine a sample of 94 people who answered. Primary data were obtained through questionnaires and analyzed using multiple linear regression using SPSS 23. Studies show that taxpayer awareness does not affect their compliance. On the other hand, tax socialization and tax sanctions significantly and positively affect the compliance of reclamation taxpayers. This shows how important training and law enforcement are in improving tax compliance.”